Survival among children with "Lethal" congenital contracture syndrome 11 caused by novel mutations in the gliomedin gene (GLDN). Issue 11 (17th August 2017) - Wambach, Jennifer A.; Stettner, Georg M.; Haack, Tobias B.; Writzl, Karin; Škofljanec, Andreja; Maver, Aleš; Munell, Francina; Ossowski, Stephan; Bosio, Mattia; Wegner, Daniel J.; Shinawi, Marwan; Baldridge, Dustin; et al.
Abstract: Biallelic GLDN mutations have recently been identified among infants with lethal congenital contracture syndrome 11 (LCCS11). GLDN encodes gliomedin, a protein required for the formation of the nodes of Ranvier and development of the human peripheral nervous system. We report six infants and children from four unrelated families with biallelic GLDN mutations, four of whom survived beyond the neonatal period into infancy, childhood, and late adolescence with intensive care and chronic respiratory and nutritional support. Our findings expand the genotypic and phenotypic spectrum of LCCS11 and demonstrate that the condition may not necessarily be lethal in the neonatal period. Abstract : GLDN encodes gliomedin which is required for the formation of the nodes of Ranvier and development of the human peripheral nervous system. Biallelic GLDN mutations have been identified among infants with lethal congenital contracture syndrome 11 (LCCS11). Here, we report 6 additional infants and children with biallelic GLDN mutations and arthrogryposis, some of whom survived into infancy, childhood and even late adolescence with chronic respiratory and nutritional support.